Sistem Presensi Mahasiswa Berbasis Animated QR Code Menggunakan Raspberry Pi - Michael Anggreawan Alexander; Justinus Andjarwirawan; Indar Sugiarto (Jurnal Infra, 2020)
Now the use of technology in the field of information systems technology has expanded more widely in all fields, including in educational institutions. The current presence system that is currently running on the teaching and learning system in several educational institutions still uses conventional methods. This causes need more time in the presence process. Previous research has implemented a QR Code added to the Mobile System application. Presence features using the QR Code can be found on the Schedule and Absentee menus. The presence will automatically follow the number of meetings that have been conducted.So with this description will be done designing and creating a presence system workflow with optimizing QR Code that is equipped with Animated, so that it can run using the Android application and using the Raspberry Pi 4 system which is equipped with a camera to read the Animated QR Code, where the student data will be sent to the database using Internet connectivity.Based on the results of tests that have been done, students managed to get an Animated QR Code as presence data by logging in to the application that is incorporated in the Internet network and storing the presence data in the Database. Raspberry Pi Camera is able to read Animated QR Codes from the Android application by taking a few seconds using Raspberry Pi 4. Facilitates students in making presence using an Android-based application.